Design and preparation of a fluorescent molecularly imprinted membrane for the selective detection of pepsin enzyme as a biomarker for gastroesophageal reflux disease - Aya M. Mostafa; Stephen J. Barton; Stephen P. Wren; James Barker (Talanta Open)
A novel fluorescent molecularly imprinted polymer membrane (FMIM) has been developed for the selective binding and qualitative detection of pepsin enzyme, a biomarker indicative of gastroesophageal reflux disease (GERD). This study utilises the high selectivity offered by molecular imprinting techniques to capture pepsin enzyme within complex biological matrices, such as human saliva. Additionally, fluorescent carbon dots integrated into the membrane matrix provide instant visual detection of pepsin. Various combinations of functional monomers and cross-linkers were systematically evaluated to investigate their impact on the binding capacity and mechanical stability of the resultant FMIMs. The optimum performance was achieved with a mixture of two hydrophilic monomers, namely N-(hydroxymethyl)acrylamide and acrylamide, in conjunction with N,N-methylenebis(acrylamide) as the cross-linking agent. The developed FMIM demonstrated a binding capacity of 21.56 mg g-1, surpassing that of the fluorescent non-imprinted membrane (FNIM) at 8.49 mg g-1. Moreover, the binding of FMIM to pepsin was tested against other competitor enzymes to verify its selectivity. Furthermore, comprehensive characterisation of both FMIM and FNIM was conducted using various analytical techniques to ensure their structural integrity and functionality. Ultimately, the developed FMIM exhibited effective binding of pepsin in standard solutions and samples, enabling enrichment and visual detection of the biomarker enzyme.